Yttrium-doped NiMo-MoO2 heterostructure electrocatalysts for hydrogen production from alkaline seawater - Shujie Liu; Zhiguo Zhang; Kamran Dastafkan; Yan Shen; Chuan Zhao; Mingkui Wang (Nature Communications)
Abstract Active and stable electrocatalysts are essential for hydrogen production from alkaline water electrolysis. However, precisely controlling the interaction between electrocatalysts and reaction intermediates (H2O*, H*, and *OH) remains challenging. Here, we demonstrate an yttrium-doped NiMo-MoO2 heterogenous electrocatalyst that efficiently promotes water dissociation and accelerates the intermediate adsorption/desorption dynamics in alkaline electrolytes. Introducing yttrium into the NiMo/MoO2 heterostructure induces lattice expansion and optimizes the d-band center of NiMo alloy component, enhancing water dissociation and H* desorption. Yttrium doping also increases the concentration of oxygen vacancies in MoO2−x, which in turn accelerates the charge kinetics and the swift evacuation of *OH intermediates from the active sites. Consequently, the Y-NiMo/MoO2−x heterostructure exhibits notable performance by requiring only 189 and 220 mV overpotentials to achieve current density of 2.0 A cm−2 in alkaline water and seawater, respectively. This work provides a strategy to modulate heterostructure catalysts for scalable, economically viable hydrogen production from low-quality waters.